A Guide to Creating and Testing New INTRSECT Constructs. Issue 1 (13th February 2018) - Fenno, Lief E.; Mattis, Joanna; Ramakrishnan, Charu; Deisseroth, Karl
Abstract: As the power of genetically encoded interventional and observational tools for neuroscience expands, the boundaries of experimental design are increasingly defined by limits in selectively expressing these tools in relevant cell types. Single‐recombinase‐dependent expression systems have been widely used as a means to restrict gene expression based on single features by combining recombinase‐dependent viruses with recombinase‐expressing transgenic animals. This protocol details how to create INTRSECT constructs and use multiple recombinases to achieve targeting of a desired gene to subsets of neurons that are defined by multiple genetic and/or topological features. This method includes the design and utilization of both viruses and transgenic animals: these tools are inherently flexible and modular and may be used in different combinations to achieve the desired gene expression pattern. © 2017 by John Wiley & Sons, Inc.